Collaborative Leadership Model In MSME Development - Syah, Toufan Aldian (DAS Institute, 2025)
This study aims to evaluate collaborative leadership in the development of Micro, Small, and Medium Enterprises (MSMEs) in the eyelash production center of Purbalingga Regency. Using a descriptive qualitative approach, data were obtained through in-depth interviews with three MSME actors and one manager of a sharia cooperative, supported by observation and documentation. The findings indicate that government support remains normative and populist, access to funding is inconsistent, and collaborative leadership practices are underdeveloped. The study emphasizes the need for a structured collaborative leadership model to strengthen the MSME ecosystem sustainably. It proposes the importance of active participation, the role of community leaders, and cross-sectoral synergy as strategies for institutional strengthening of MSMEs.